PERSEPSI PENGUNJUNG PADA OBJEK WISATA DANAU BUATAN KOTA PEKANBARU - Osman Ananto; Mariaty Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research purposed to get how perception or anxiety visitors and hope them to tourist attraction danau buatan at Pekanbaru city . This research used qualitative descriptive method to analyze the problems. The sample in this research are seven samples get by snowball sampling. And then the technique to collected data in this research are using observation and deep interview . Based on the research, perception visitors about tourist attraction danau buatan has analized based on three variables which includes cognitive, affective, and conative These three aspects are knowledge, understanding, views, feeling ,emotions, attitudes, judgments, motivations, driving factors, the willingness and desire of visitors and hope in the future to tourist attraction danau buatan at Pekanbaru city. Where the ultimate goal of everything to be tourist atraction danau buatan more complete both facilities and infrastructure, maintenance, visitos comfort , and increased number of visits. Key words : Perception of visitors , Hope Visitors, Danau Buatan